Investigating the mediating influence of teachers' job satisfaction on the relationship between teachers' leadership and teachers' job performance in China - Zhang, Jing (2025)
Teacher leadership plays a vital role in enhancing the quality of education. However, in China, research on this topic remains limited and does not have a clear definition. Previous studies have also indicated that internal factors, such as job satisfaction, influence teacher leadership in this context. Therefore, the purpose of this study was to examine the influence of teachers’ job satisfaction on the relationship between teacher leadership and teacher job performance in China. This study employed a quantitative cross-sectional survey design. Data were collected using questionnaires from 359 secondary school teachers in Shaanxi Province, China, selected through stratified random sampling. Three main variables were examined, which are teacher leadership, job satisfaction, and job performance. Data analysis involved descriptive statistics, inferential analysis, and Structural Equation Modelling (SEM) using SPSS and AMOS version 29. The findings of the study showed that teacher leadership significantly and positively influences both job satisfaction and job teacher performance. Teachers’ job satisfaction was found to be a partially mediator of the relationship between teacher leadership and job performance. Additionally, this study successfully developed a structural model that links teachers’ leadership, job satisfaction, and teacher job performance. This study contributes to the theoretical understanding of educational leadership by clarifying the mechanism linking leadership and teacher performance. Besides that, it also has practical implications for policymakers and school administrators to enhance the leadership effectiveness, job satisfaction, and teacher performance. However, it is suggested to future researchers further expand the location of the study and improve the research design to yield more consistent findings, particularly in the context of educational environment in China